1997
DOI: 10.1152/ajplung.1997.272.1.l20
|View full text |Cite
|
Sign up to set email alerts
|

Strain increases airway smooth muscle contractile and cytoskeletal proteins in vitro

Abstract: Mechanical stress contributes to lung development and the progression of some lung diseases, although its effects on individual lung cells are unknown. Because increased airway smooth muscle (ASM) is found in lung diseases where abnormal stress is present, we determined if strain (change in resting length) causes ASM hypertrophy independently of other in vivo influences. Cultured canine ASM cells were subjected to two levels of cyclic deformational strain for 14 days and compared with nonstrained cells by sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 0 publications
4
51
0
2
Order By: Relevance
“…These observations are consistent with decreased Rho activation, which is in contrast to the increased Rho-A activation observed in response to predominantly uniaxial strain [231] and would appear to represent anticontractile effects of strain rather than pro-contractile effects of strain as occurring with primarily uniaxial strain. Furthermore, increases in amount of myosin light chain kinase after 11 days of strain seem to occur primarily in uniaxially strained cells [243,246]. Interestingly, proliferation is reduced in cells grown on laminin and subjected to lower strains of 4% compared with cells grown on collagen with either 0 or 4% strain.…”
Section: Chronic Oscillatory Length Change In Cultured Asm Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…These observations are consistent with decreased Rho activation, which is in contrast to the increased Rho-A activation observed in response to predominantly uniaxial strain [231] and would appear to represent anticontractile effects of strain rather than pro-contractile effects of strain as occurring with primarily uniaxial strain. Furthermore, increases in amount of myosin light chain kinase after 11 days of strain seem to occur primarily in uniaxially strained cells [243,246]. Interestingly, proliferation is reduced in cells grown on laminin and subjected to lower strains of 4% compared with cells grown on collagen with either 0 or 4% strain.…”
Section: Chronic Oscillatory Length Change In Cultured Asm Cellsmentioning
confidence: 95%
“…These changes depend on strain magnitude and orientation, as discussed in sections below. In several studies, SMITH and coworkers [230,[242][243][244] have demonstrated that a predominantly uniaxial (stretch in one direction) strain of ,10% applied for several days in culture increases proliferation, force generation, expression of contractile proteins, calcium sensitivity and cytoskeletal stiffness with contractile activation. Perhaps the most dramatic changes they have been shown are a doubling in shortening capacity and shortening velocity [245].…”
Section: Chronic Oscillatory Length Change In Cultured Asm Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine GЈ using OMTC, we grew cells to ϳ90% confluence and then changed them to serum-free media supplemented with insulin and transferrin as previously described (21). After a rinse with PBS, membranes were cut from the six-well plates with a scalpel and placed in serumfree media.…”
Section: Methodsmentioning
confidence: 99%
“…Οι ΛΜΙ αλλάζουν μήκος και φορτίο κατά τη διάρκεια της εισπνοής και της εκπνοής και οι μεταβολές αυτές του μήκους επηρεάζουν τη διάμετρο των αεραγωγών και κατά συνέπεια τη ροή του αέρα προς τους πνεύμονες. Αυτές οι μεταβολές του μήκους επιφέρουν αλλαγές στην τάση (ενεργή και παθητική) που αναπτύσουν οι ΛΜΙ [48,49] . Η παθητική τάση η οποία αναπτύσσουν οι ΛΜΙ είναι ένας σημαντικός παράγοντας για τον καθορισμό της ανταποκρισιμότητας των ΛΜΙ των αεραγωγών στην επίδραση συσπαστικών παραγόντων και φαίνεται να εμπλέκεται στην παθογένεση των αποφρακτικών νόσων των αεραγωγών όπως είναι η χρόνια αποφρακτική πνευμονοπάθεια και το άσθμα [9] .…”
Section: ο ρόλος του φορτίου στη σύσπαση των λμιunclassified